A prototype optical link board with redundancy design for the ATLAS liquid argon calorimeter Phase-2 upgrade. (1st May 2022) - Huang, X.; Liu, C.; Deiana, A.; Deng, B.; Gong, D.; Hasley, L.; Hou, S.; Liu, T.; Sun, H.; Ye, J.; Zhang, L.; Zhang, W.
Abstract: A prototype optical-link board has been developed for the ATLAS Liquid Argon Calorimeter Phase-2 upgrade. The board consists of 24 lpGBT chips and 8 VTRx+ modules and demonstrates the full optical link design of the future front-end board. The board has 22 simplex optical links to transmit detector data, which are emulated in FPGAs and injected through 6 FMC connectors, to the off-detector electronics. The board implements 2 duplex optical links for clocks, control, and monitoring with redundant design to improve the system reliability. Data transmission and all redundant designs have been verified. A fiber routing scheme, in which 2 or 3 VTRx+ modules are re-connected to the front panel with an MPO connector, has been prototyped.